2007
DOI: 10.1002/hipo.20264
|View full text |Cite
|
Sign up to set email alerts
|

Infusion of neuropeptide Y into CA3 region of hippocampus produces antidepressant‐like effect via Y1 receptor

Abstract: A couple of papers indicate that patients with depression show a decrease in serum neuropeptide Y (NPY). To study the role of NPY in depression, we examined the effects of infusion of NPY into the hippocampus of learned helplessness (LH) rats (an animal model of depression). Infusion of NPY into the cerebral ventricle of LH rats showed antidepressant-like effects. Infusion of NPY into the CA3 region, but not the dentate gyrus (DG), produced antidepressant-like effects in the LH paradigm. Infusion of NPY did no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 73 publications
3
39
0
Order By: Relevance
“…14) In addition, in the learned helplessness model, acute infusion of NPY in the CA3 of the hippocampus produced an antidepressant-like effect. 15) TRH mRNA increases occurred only after chronic ECS in the hippocampus. This increase is consistent with the ability of ECS to increase prepro-TRH peptides in several rat brain regions and with the antidepressant-like effects of TRH in the rodent forced swim test.…”
Section: Regulation Of Gene Expression In Hippocampus By Ecs Treatmentmentioning
confidence: 89%
“…14) In addition, in the learned helplessness model, acute infusion of NPY in the CA3 of the hippocampus produced an antidepressant-like effect. 15) TRH mRNA increases occurred only after chronic ECS in the hippocampus. This increase is consistent with the ability of ECS to increase prepro-TRH peptides in several rat brain regions and with the antidepressant-like effects of TRH in the rodent forced swim test.…”
Section: Regulation Of Gene Expression In Hippocampus By Ecs Treatmentmentioning
confidence: 89%
“…[15][16][17][18][19][20] In addition, it has been reported that the reduced hippocampal NPY levels in animal models of depression were restored by treatment with antidepressants, 12,15,21) electroconvulsive stimuli, [16][17][18][19] and running. 22) Moreover, additional evidence has shown that NPY per se exhibits antidepressantlike activity via the Y1 receptor [23][24][25][26] and promotes the proliferation of hippocampal neural progenitor cells.…”
Section: Neuropeptide Y (Npy) and Orexin-a (Ox-mentioning
confidence: 99%
“…[15][16][17][18][19][20] In addition, it has been reported that the reduced hippocampal NPY levels in animal models of depression were restored by treatment with antidepressants, 12,15,21) electroconvulsive stimuli, [16][17][18][19] and running. 22) Moreover, additional evidence has shown that NPY per se exhibits antidepressantlike activity via the Y1 receptor [23][24][25][26] and promotes the proliferation of hippocampal neural progenitor cells.27-31) These findings suggest that the upregulation of hippocampal cell proliferation and neurogenesis, the downregulation of which is inversely associated with the pathology of depression, 32,33) could be required for NPY-induced antidepressant-like effects.In clinical studies, some reports have suggested that NPY levels in the cerebrospinal fluid are decreased in patients with major depression [34][35][36][37] and that the NPY levels are improved by electroconvulsive therapy 38) and treatment with an antidepressant. 39) Improvement in the dysfunction of the NPY system might alleviate some afflictions in patients with major depression.…”
mentioning
confidence: 99%
“…NPY itself has been shown to have antidepressant-like activity. Intracerebroventricular injections of NPY or NPY receptor 1 (Y 1 ) agonists significantly reduced immobility time in both the FST (Husum et al, 2000;Stogner and Holmes, 2000;Redrobe et al, 2002a) and LH paradigms (Ishida et al, 2007). However, the role of VGF in depression has not been explored.…”
Section: Vgf In Depression Modelsmentioning
confidence: 99%